Evaluation of Cardio-Ankle Vascular Index and Influencing Factors in Natural Population of She Minority in China - Huan Liu; Yongqiang Hong; Xiuqin Wu; Xiaobin Zhang; Menghua Huang; Hongyu Wang (Internal Medicine, 2016)
Objective: The present study was designed to investigate the influencing factor of cardio-ankle vascular index (CAVI) in natural population of She minority in China. Methods: Five hundred and twenty-four subjects were enrolled into our study (male 227 and female 297). Main analyzing indexes included vascular related markers namely of CAVI and carotid artery intima-media thickness (CIMT) and blood markers. Results: Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were high in the entire population (150.08±23.32 mmHg, 91.15±12.42 mmHg). CAVI, left CIMT and right CIMT were normal. Univariate analysis showed CAVI was positively correlated with age, waist hip ratio (WHR), SBP, DBP, pulse pressure (PP), blood urea nitrogen (BUN), serum creatinine (Cr), fasting plasma glucose (FPG), triglyceride (TG), total cholesterol (TC), low density lipoprotein cholesterol (LDL-C), high sensitive C reactive protein (hs-CRP), left CIMT and right CIMT (r=0.570, 0.240, 0.512, 0.372, 0.459, 0.231, 0.095, 0.182, 0.158, 0.164, 0.167, 0.169, 0.395, 0.407, all p<0.05). Multivariate linear regression analysis (selected factors including age, heart rate (HR), body mass index (BMI), WHR, SBP, DBP, PP, blood uric acid (UA), BUN, Cr, FPG, TC, TG, high density lipoprotein cholesterol (HDL-C), LDL-C, hs-CRP, left CIMT and right CIMT) showed that age, SBP, FPG, hs-CRP, TG and Cr were the independent related factors of CAVI (adjusted R2=0.399). Conclusion: Age, systolic blood pressure, fasting plasma glucose, high sensitive C-reactive protein, triglyceride and creatinine levels were independent factors of CAVI in natural populations of She minority in China.